Pengaruh Dow Jones Islamic Market (DJIM), Kurs, Dan Harga Emas Dunia Terhadap Jakarta Islamic Indeks (JII) Periode 2016-2018 - Agus Salihin (Jurnal Istiqro, 2019)
The purpose of this study was to determine the effect of Dow Jones Islamic Market (DJIM), Exchange Rate, and World Gold Prices on the Jakarta Islamic Index (JII) for the 2016-2018 Period. This type of research uses quantitative research, namely by estimating the regression model of time series data usage. The data used is secondary data with a time period of 3 (three) years, namely 2016-2018. Data analysis techniques in this study using multiple linear regression analysis techniques with the help of SPSS 16.0 Program. Based on the analysis results, it can be concluded that partially the Dow Jones Islamic Market Index (DJIM) and Exchange Rate have a significant positive effect on the Jakarta Islamic Index (JII). While the World Gold Price has no significant positive effect on the Jakarta Islamic Index (JII) for the 2016-2018 period. Simultaneously, the Dow Jones Isamic Market Index (DJIM), Dinia Gold Exchange Rate and Price have a significant effect on the Jakarta Islamic Index (JII) for the 2016-2018 Period.